"LIP" the Living with illness programme. Issue 2 (1st September 2011) - Argent, Ian
Abstract : Introduction: For around 3 years, St Helena Hospice's LIP programme has brought together patients and carers to an informative, supportive forum. The rolling programme of semi-structured sessions is intended to enhance awareness and choice by raising important issues early on in the 'journey'. Aims: The programme has three main aims: to provide information on key 'Quality of Life' issues for those coping with illness; to facilitate discussion and understanding between patients and carers around these key issues; and to provide support from professionals and other group members. These aims tie in well with NICE guidance for psychosocial support, and with the NCPC's initiative "Dying Matters". Method: The 6-week LIP is built around themes identified from previous groups at the Hospice (eg, Families and Feelings, Intimacy and Sexuality, Lifestyle and Coping, and Planning for Future Care). Each 90-min session is run by a relevant professional, with a co-ordinator/facilitator present throughout for continuity. The theme for each session is used as a starting-point for information and discussion. What follows is a more open, free-flowing group time, where issues important to the group members are shared and reflected upon. An anonymous feedback questionnaire is sent to participants after the programme's end. Results and discussion: Group numbers vary from 8 to 20+, with a good mixture of patients and carers. The weekly themes certainly provide a stimulus for group discussions in-session. There is an important added effect of more conversations taking place at home, within couples and families. Feedback has prompted some changes, but in general the programme is well-received by participants. Anecdotal evidence suggests that patients and carers have benefited from the early input of appropriate material, as this enhances their informed decision-making later on in areas such as Preferred Priorities of Care, funeral planning, etc.